Positive pole piece and preparation method thereof, secondary battery and electronic device
By designing a reasonable insulating layer and positive electrode material layer structure in the positive electrode sheet of the multi-pole ear secondary battery, the short circuit problem caused by the contact between the electrode and the negative electrode sheet is solved, and the tensile strength and safety performance are improved.
Patent Information
- Application Number
- CN202510111774.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-05-02
AI Technical Summary
During the production process of multi-pole ear secondary batteries, the ears of the positive electrode sheet come into contact with the negative electrode sheet, causing a short circuit, resulting in stress concentration and wrinkle deformation in the empty foil area, reducing tensile strength and safety performance.
A positive electrode sheet is designed, which includes a positive electrode current collector, a positive electrode material layer and an insulating layer. By adjusting the connection method between the insulating layer and the positive electrode material layer and the ratio of the adhesive and ceramic materials, the tensile strength and insulation performance are improved.
It effectively improves the tensile strength of the positive electrode plate, reduces the risk of the extreme ear fracture, and improves the safety performance and energy density of the secondary battery.
Smart Images

Figure CN119920828A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a positive electrode sheet and a preparation method thereof, a secondary battery and an electronic device. Background Art
[0002] With the advancement of technology, the performance of secondary batteries is constantly improving, and their application areas are also expanding. Multi-pole secondary batteries are an effective technical improvement to meet the current demand for fast charging. The multi-pole design can significantly improve the charging efficiency of secondary batteries.
[0003] In the manufacturing process of multi-electrode secondary batteries, the method of applying an insulating layer on the edge of the positive electrode material layer is usually adopted to prevent the tab of the positive electrode sheet from contacting the negative electrode sheet and causing a short circuit. However, during the cold pressing process, stress concentration will occur at the junction of the area where the positive electrode material layer is set in the positive electrode sheet and the empty foil area, causing wrinkles and deformation of the empty foil area near the junction, which not only reduces the tensile strength of the empty foil area, but also affects the subsequent coating of the insulating layer, reducing the overall reliability of the positive electrode sheet. Therefore, during the use of multi-electrode secondary batteries, the positive electrode sheet is prone to breakage at the edge of the positive electrode material layer, which greatly affects the safety performance of the secondary battery. Summary of the invention
[0004] The purpose of this application is to provide a positive electrode sheet and a preparation method thereof, a secondary battery and an electronic device, so as to improve the overall tensile strength of the positive electrode sheet of the secondary battery, thereby improving the safety performance of the secondary battery. The specific technical solution is as follows:
[0005] It should be noted that in the invention content of the present application, a lithium-ion battery is used as an example of a secondary battery to explain the present application, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0006] The first aspect of the present application provides a positive electrode sheet, which includes a positive current collector, a positive electrode material layer, and an insulating layer. The positive electrode sheet includes a hollow foil area and a coating area. The positive electrode material layer and the insulating layer are located in the coating area. The insulating layer and the positive electrode material layer are connected along the length direction of the positive current collector, and the insulating layer is closer to the hollow foil area than the positive electrode material layer; along the direction from the positive electrode material layer to the insulating layer, the positive electrode material layer includes a first edge and a second edge relative to each other, and the first edge is close to the hollow foil area; the positive electrode sheet is subjected to a tensile strength test, and the fracture position of the positive electrode sheet is located between the first edge and the second edge, and the distance between the fracture position and the first edge is x mm, 3<x≤20. In some embodiments of the present application, 5<x≤20. Through the above arrangement, it is not only beneficial to improve the tensile strength near the positive electrode ear, but also reduce the risk of fracture of the positive electrode ear, thereby improving the safety performance of the secondary battery.
[0007] In some embodiments of the present application, the tensile strength of the hollow foil area and the area where the insulating layer is set in the positive electrode plate is R1 MPa, and the tensile strength of the area where the positive electrode material layer is set in the positive electrode plate is R2 MPa, 220≤1.2R2<R1≤280. By R1 and R2 being within the above range, the tensile strength of the positive electrode tab is improved, which is conducive to reducing the risk of positive electrode tab breakage, thereby improving the safety performance of the secondary battery.
[0008] In some embodiments of the present application, the difference between the maximum thickness and the minimum thickness of the positive electrode material layer is less than or equal to 1 μm. In some embodiments of the present application, the difference between the maximum thickness and the minimum thickness of the positive electrode material layer is less than or equal to 0.8 μm. The above arrangement is conducive to improving the energy density of the secondary battery. At the same time, the distance between the fracture position and the first edge is within the above range, which is conducive to improving the tensile strength near the positive electrode ear, reducing the risk of fracture of the positive electrode ear, and improving the safety performance of the secondary battery.
[0009] In some embodiments of the present application, the roughness of the empty foil area is Rzμm, 2≤Rz≤5. By regulating Rz within the above range, it is not only helpful to reduce the risk of positive electrode tab breakage, but also the positive electrode current collector with the above roughness is conducive to the subsequent insulating layer firmly attached to the positive electrode current collector and not easy to fall off, thereby improving the safety performance of the secondary battery.
[0010] In some embodiments of the present application, the insulating layer includes a binder and a ceramic material, and the insulating layer satisfies at least one of the following characteristics: (1) based on the mass of the insulating layer, the mass percentage content W1 of the binder is 5% to 20%; (2) based on the mass of the insulating layer, the mass percentage content W2 of the ceramic material is 80% to 95%. By regulating the mass percentage content of the binder and the ceramic material of the insulating layer to meet at least one of the above, the insulation performance of the positive electrode tab can be improved, thereby improving the safety performance of the secondary battery.
[0011] In some embodiments of the present application, the insulating layer includes a binder and a ceramic material, and the insulating layer satisfies at least one of the following characteristics: (1) based on the mass of the insulating layer, the mass percentage content W1 of the binder is 70% to 90%; (2) based on the mass of the insulating layer, the mass percentage content W2 of the ceramic material is 10% to 30%. By regulating the mass percentage content of the binder and the ceramic material of the insulating layer to meet at least one of the above, it is beneficial to promote the insulating layer to have both good flexibility and insulation performance, which is beneficial to improve the pass rate of the secondary battery in the drop test and improve the safety performance of the secondary battery.
[0012] In some embodiments of the present application, the insulating layer satisfies at least one of the following characteristics: (1) the binder includes at least one of polyurethane, polyacrylic acid or polyacrylonitrile; (2) the ceramic material includes at least one of boehmite or alumina. By selecting the above binder and / or ceramic material, the insulating layer has good insulating properties and is not easy to fall off when the secondary battery is working, which is conducive to improving the cycle stability and safety performance of the secondary battery.
[0013] In some embodiments of the present application, the maximum thickness of the insulating layer is d μm and the width is b mm, wherein 10≤d≤40 and 1.5≤b≤3.5. In some embodiments of the present application, 10≤d≤25; and / or, 2.0≤b≤3.0. By regulating d and b within the above ranges, the energy density and safety performance of the secondary battery can be balanced, so that the secondary battery has a higher energy density while having a higher safety performance.
[0014] In some embodiments of the present application, the edge of the insulating layer close to the positive electrode material layer is the third edge, and the third edge coincides with the first edge, or the third edge is located between the first edge and the second edge, and the distance between the third edge and the first edge is s mm, 0≤s≤0.5. In some embodiments of the present application, 0≤s≤0.3. By regulating the distance s between the third edge and the first edge within the scope of the present application, it is beneficial to promote the secondary battery to have higher safety performance and higher energy density.
[0015] In some embodiments of the present application, the positive electrode material layer and the insulating layer are arranged on the two surfaces of the coating area, and the distance between the third edges of the insulating layer on both sides of the positive electrode current collector along the direction from the positive electrode material layer to the insulating layer is Δs mm, 0≤Δs≤0.3. In some embodiments of the present application, 0≤Δs≤0.1. By regulating the distance Δs between the third edges of the insulating layer on both sides of the positive electrode current collector within the above range, it is beneficial to improve the tensile strength near the positive electrode tab, reduce the risk of positive electrode tab fracture, and increase the proportion of the positive electrode material layer by improving the setting accuracy of the insulating layer, thereby helping to improve the energy density of the secondary battery.
[0016] In some embodiments of the present application, the positive electrode material layer and the insulating layer are arranged on the two surfaces of the coating area, and the maximum thickness difference of the insulating layer on both sides of the positive electrode current collector is Δd μm, 0≤Δd≤15. In some embodiments of the present application, 0≤Δd≤10. By regulating the value of Δd within the above range, it is beneficial to improve the insulation performance near the positive electrode tab, reduce the risk of fracture of the positive electrode tab, and improve the safety performance of the secondary battery.
[0017] In some embodiments of the present application, the positive electrode material layer and the insulating layer are arranged on the two surfaces of the coating area, and the difference in width of the insulating layer on both sides of the positive electrode current collector is Δb mm, 0≤Δb≤0.3. By regulating Δb within the above range, it is not only beneficial to improve the tensile strength of the positive electrode tab, reduce the risk of positive electrode tab fracture, but also improve the accuracy and increase the proportion of the positive electrode material layer, thereby improving the energy density.
[0018] In some embodiments of the present application, the thickness of the positive electrode current collector is hμm, 8≤h≤10. By selecting the positive electrode current collector within the above range, the strength of the positive electrode pole piece during cold pressing and processing can be guaranteed, and the risk of band breakage during pole piece processing and subsequent pole ear breakage can be reduced. At the same time, the use of a positive electrode current collector with a relatively low thickness is conducive to the improvement of energy density, achieving the purpose of taking into account processing stability, safety, and energy density.
[0019] The second aspect of the present application provides a method for preparing a positive electrode pole piece in any of the aforementioned embodiments, which comprises the following steps: obtaining a positive electrode material layer slurry and an insulating layer slurry; setting adhesive paper in the first and second regions of the positive electrode current collector, and then setting the positive electrode material layer slurry in the third region of the positive electrode current collector and making at least part of the surface of the adhesive paper covered by the positive electrode material layer slurry, and then drying and cold pressing, and then peeling off the adhesive paper, setting the insulating layer slurry in the second region, and drying to obtain a positive electrode pole piece; wherein the first region is an empty foil region, the second region is used to set the insulating layer, and the third region is used to set the positive electrode material layer, and the first region, the second region and the third region are connected in sequence.
[0020] A third aspect of the present application provides a secondary battery, which includes the positive electrode sheet in any of the aforementioned embodiments or the positive electrode sheet obtained according to the aforementioned preparation method.
[0021] A fourth aspect of the present application provides an electronic device, which includes the secondary battery in any of the aforementioned embodiments.
[0022] Beneficial effects of this application:
[0023] The present application provides a positive electrode sheet and a preparation method thereof, a secondary battery and an electronic device, wherein the positive electrode sheet comprises a positive current collector, a positive electrode material layer, and an insulating layer, wherein the positive electrode sheet comprises an empty foil area and a coating area, wherein the positive electrode material layer and the insulating layer are located in the coating area, wherein the insulating layer and the positive electrode material layer are sequentially connected, and wherein the insulating layer is closer to the empty foil area than the positive electrode material layer; wherein the positive electrode material layer comprises a first edge and a second edge relative to each other along the direction from the positive electrode material layer to the insulating layer, wherein the first edge is closer to the empty foil area; wherein a 5mm×30mm positive electrode sheet is used for a tensile strength test, wherein the fracture position of the positive electrode sheet is located between the first edge and the second edge, and the distance between the fracture position and the first edge is x mm, and 20≥x>3. By controlling x within the above range, the positive electrode material layer has a higher strength near the first edge, which is conducive to reducing the possibility of fracture near the first edge of the positive electrode material layer, thereby reducing the fracture risk of the positive electrode tab, improving the safety performance of the secondary battery and taking into account the energy density.
[0024] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0026] Figure 1 A schematic diagram of the cross-sectional structure of a positive electrode sheet along its thickness direction in one embodiment of the present application;
[0027] Figure 2 A schematic diagram of the cross-sectional structure of a positive electrode sheet along its thickness direction in another embodiment of the present application;
[0028] Figure 3 This is a schematic diagram of the cross-sectional structure of a positive electrode sheet along its thickness direction in another embodiment of the present application;
[0029] Figure 4 This is a schematic diagram of the cross-sectional structure of a positive electrode sheet along the thickness direction in another embodiment of the present application;
[0030] Figure 5 A schematic diagram of the structure of a lithium-ion battery in one embodiment of the present application;
[0031] Figure 6a This is a photo of the positive electrode plate test sample in Comparative Example 1 after the tensile strength test;
[0032] Figure 6bThis is a photo of the positive electrode plate test sample in Example 1-5 after the tensile strength test;
[0033] Figure 7a This is a tensile curve test diagram of the test sample of the positive electrode sheet in Comparative Example 1;
[0034] Figure 7b This is a tensile curve test diagram of the test sample of the positive electrode sheet in Example 1-5;
[0035] Figure 8a This is an electron microscope photograph of a sample obtained by providing only a positive electrode material layer on the surface of the positive electrode current collector in Comparative Example 1 after cold pressing;
[0036] Figure 8b This is an electron microscope photograph of the sample obtained by providing only a positive electrode material layer on the surface of the positive electrode current collector in Example 1-5 after cold pressing and removing the adhesive tape. DETAILED DESCRIPTION
[0037] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0038] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0039] At present, in order to meet the needs of fast charging, secondary batteries usually adopt a multi-pole lug design. The pole lug is usually an extension of the current collector and acts as a conductor. Each pole lug is the current output point of the positive electrode plate or negative electrode plate where it is located. The positive pole lug of the secondary battery is obtained by stacking multiple positive pole lugs and then transfer welding, and the negative pole lug of the secondary battery is obtained by stacking multiple negative pole lugs and then transfer welding, so as to achieve a parallel effect, so that the secondary battery can be charged and discharged at a large rate, such as 5C, 10C or even higher rates, to meet the needs of fast charging.
[0040] Among them, the positive electrode sheet is usually prepared by the "zebra coating" process. Due to the surface tension of the positive electrode material layer slurry during the coating process, the thickness of the edge area of the obtained positive electrode material layer is less than the thickness of the central area of the positive electrode material layer, that is, a "thinning area" will appear at the edge of the positive electrode material layer. In the preparation process of the positive electrode sheet of the secondary battery, the positive electrode material layer needs to be cold pressed. During the cold pressing process, there is usually a stress concentration phenomenon at the junction between the area of the positive electrode material layer and the empty foil area, which makes the empty foil area near the junction prone to wrinkling and deformation. The area near the junction becomes the "weak area" of the positive electrode sheet and is prone to fracture. Since the positive electrode ear is usually set at the edge of the positive electrode sheet, that is, near the above-mentioned junction, it will increase the risk of positive electrode ear fracture, thereby affecting the safety performance of the lithium-ion battery. In addition, for multi-electrode secondary batteries, an insulating layer is usually set at the edge of the positive electrode material layer to reduce the risk of short circuit between the positive electrode tab and the negative electrode sheet in the positive electrode collector, and improve the safety performance of the secondary battery. However, during the cold pressing process, due to the stress concentration at the edge of the positive electrode material layer, the positive electrode collector is prone to wrinkling and deformation, which will also affect the setting of the insulating layer. In particular, for positive electrode sheets without a "thinning area", they often face greater stress concentration during the cold pressing process, thus affecting the safety performance of the secondary battery.
[0041] The solution of the present application can be used in the design of positive electrode material layers with or without thinning areas, which can reduce the risk of positive electrode tab fracture, thereby improving the safety performance of secondary batteries. Based on the above problems, the present application provides a secondary battery and an electronic device to improve the problem that the empty foil area near the junction is prone to wrinkling and deformation, reduce the risk of positive electrode tab fracture, and thereby improve the safety performance of secondary batteries.
[0042] The first aspect of the present application provides a positive electrode sheet, such as Figure 1 As shown, the positive electrode sheet 01 includes a positive electrode current collector 10, a positive electrode material layer 20, and an insulating layer 30. The positive electrode sheet 01 includes a hollow foil area 012 and a coating area 011. The positive electrode material layer 20 and the insulating layer 30 are located in the coating area 011. Along the length direction of the positive electrode current collector 10, the insulating layer 30 and the positive electrode material layer 20 are connected and arranged. The "length direction" refers to the length direction of the positive electrode current collector 10. Figure 5 the direction indicated by the rightmost arrow, or Figure 1 In the direction from the positive electrode material layer 20 to the insulating layer 30, the insulating layer 30 is closer to the empty foil area 012 than the positive electrode material layer 20. Figure 1 In the direction indicated by the middle arrow, the positive electrode material layer 20 includes a first edge 21 and a second edge 22 opposite to each other, and the first edge 21 is close to the empty foil area 012 .
[0043] A 5mm×30mm positive electrode sheet is used for tensile strength test. The fracture position of the positive electrode sheet is located between the first edge and the second edge, and the distance between the fracture position and the first edge is x mm, 3<x≤20. In some embodiments of the present application, 5<x≤20. For example, x can be 3.5, 4, 4.5, 5, 5.5, 6, 7, 8, 9, 10, 12, 15, 17, 19, 20 or a range consisting of any two values therebetween. When x≤3, it means that when the positive electrode sheet is subjected to tensile strength test, the positive electrode sheet tends to break near the first edge. This is usually because in the cold pressing process, the stress near the first edge is more concentrated, resulting in wrinkle deformation of the empty foil area near the first edge, reducing the tensile strength of the empty foil area. Therefore, during the use of the secondary battery, the pole ear at the edge of the positive electrode sheet is prone to breakage, reducing the safety performance of the secondary battery. The 20≥x>3 in the present application means that when the positive electrode sheet is subjected to a tensile strength test, the fracture position of the positive electrode sheet is between the first edge and the second edge of the positive electrode material layer, and the distance between the fracture position and the first edge is 20≥x>3. If 20≥x>3 is within the above range, it means that the area near the first edge of the positive electrode material layer is no longer a "weak area", thereby reducing the risk of positive electrode ear fracture and improving the safety performance of the secondary battery.
[0044] Therefore, in the secondary battery provided by the present application, the problem of wrinkle deformation near the first edge of the positive electrode plate is improved, the risk of positive electrode tab breakage can be reduced, and the safety performance of the secondary battery is improved.
[0045] In this application, a 5mm×30mm positive electrode sheet sample is used for tensile strength test, wherein the size of the corresponding area of the positive electrode material layer is 5mm×25mm, and the test is performed in the direction from the positive electrode material layer to the insulating layer. Due to the different sizes of secondary batteries in actual applications, the size of the positive electrode sheet sample for tensile strength test can be determined according to the actual size of the secondary battery, and its fracture position and tensile strength will also change accordingly with the change in the size of the corresponding area of the positive electrode material layer in the positive electrode sheet sample. For example, the size of the corresponding area of the positive electrode material layer in the positive electrode sheet sample in the direction from the positive electrode material layer to the insulating layer is a, 3<x≤a-5.
[0046] In some embodiments of the present application, the difference ΔT between the maximum thickness and the minimum thickness of the positive electrode material layer is less than or equal to 1 μm. In some embodiments of the present application, the difference ΔT between the maximum thickness and the minimum thickness of the positive electrode material layer is less than or equal to 0.8 μm. For example, the difference between the maximum thickness and the minimum thickness can be 0.2 μm, 0.3 μm, 0.5 μm, 0.6 μm, 0.8 μm, 1 μm. When the difference between the maximum thickness and the minimum thickness of the positive electrode material layer 20 is within the scope of the present application, it means that there is no "thinning zone" at the edge of the positive electrode material layer, and the obtained secondary battery has a higher energy density. At the same time, the distance between the fracture position and the first edge is within the above range, which is also conducive to improving the cycle stability and safety performance of the secondary battery. Generally, the outer contour of the cross section of the positive electrode material layer without a "thinning zone" along its own thickness direction is close to a rectangle. The difference between the maximum thickness and the minimum thickness refers to the difference between the maximum thickness and the minimum thickness of the positive electrode material in the 8mm area extending from the first edge along the above direction in the direction from the insulating layer to the positive electrode material layer.
[0047] The second aspect of the present application provides a method for preparing a secondary battery in any of the aforementioned embodiments, which comprises the following steps: obtaining a positive electrode material layer slurry and an insulating layer slurry; setting adhesive paper in the first and second regions of the positive electrode current collector, and then setting the positive electrode material layer slurry in the third region of the positive electrode current collector and making at least part of the surface of the adhesive paper covered by the positive electrode material layer slurry, and then drying and cold pressing, and then peeling off the adhesive paper, setting the insulating layer slurry in the second region, and drying to obtain a positive electrode sheet; wherein the first region is an empty foil region, the second region is used to set the insulating layer, and the third region is used to set the positive electrode material layer, and the first region, the second region and the third region are connected in sequence.
[0048] Specifically, the positive electrode current collector includes the first region, the second region and the third region, wherein the first region corresponds to the empty foil region, and the second region and the third region correspond to the coated region.
[0049] In the present application, when setting the positive electrode material layer slurry, the size of the adhesive tape covering the positive electrode material layer slurry can be changed by changing the starting position of setting the positive electrode material layer slurry. Generally, the larger the size of the adhesive tape covering the positive electrode material layer slurry, the smaller the ΔT of the positive electrode material layer obtained after peeling off the adhesive tape and cold pressing, and vice versa. The above-mentioned "size of the adhesive tape covering the positive electrode material layer slurry" refers to the size of the adhesive tape covering the positive electrode material layer slurry along the direction from the insulating layer to the positive electrode material layer.
[0050] The present application has no particular restrictions on the pressure of the cold press, as long as the purpose of the present application can be achieved. For example, the pressure of the cold press can be 30t to 120t. In some embodiments of the present application, the adhesive force of the above-mentioned adhesive tape is 0.5N / m to 5N / m. The present application has no particular restrictions on the thickness of the above-mentioned adhesive tape, as long as the purpose of the present application can be achieved. For example, the thickness of the adhesive tape is 5μm to 20μm.
[0051] Thanks to the above-mentioned method for preparing the positive electrode sheet, before the positive electrode material layer slurry is set on the positive electrode current collector and cold pressed, the step of pasting adhesive tape in the area corresponding to the empty foil area and the insulating layer in the positive electrode current collector is added, that is, pasting adhesive tape in the first area and the second area, and making at least part of the surface of the adhesive tape covered by the positive electrode material layer slurry, and drying the obtained positive electrode sheet. During the cold pressing process, the area near the first edge is covered by the adhesive tape and the positive electrode material layer to form a whole, and then cold pressed, and then the adhesive tape and the positive electrode material layer on its surface are removed. Thereby achieving the purpose of protecting the empty foil area and the area corresponding to the insulating layer near the first edge of the positive electrode material layer during the cold pressing process, compared with the current setting of the positive electrode material layer or the direct cold pressing after the positive electrode material layer and the insulating layer are set at the same time, the problem of stress concentration at the junction of the coating area and the empty foil area can be improved, that is, the problem of stress concentration near the first edge, thereby alleviating the phenomenon of wrinkles near the first edge after cold pressing, improving the tensile strength of the first edge, reducing the risk of positive electrode ear fracture, and thus improving the safety performance of the secondary battery.
[0052] In some embodiments of the present application, the tensile strength of the hollow foil area and the area where the insulating layer is set in the positive electrode plate is R1 MPa, the tensile strength of the coated area is R2 MPa, and 220≤1.2R2<R1≤280. In some embodiments of the present application, 220≤R1≤280; for example, R1 can be 220, 225, 230, 235, 240, 245, 250, 255, 260, 270, 280 or a range consisting of any two of the values. In some embodiments of the present application, 190≤R2≤230; R2 can be 190, 192, 195, 200, 205, 207, 210, 212, 215, 220, 225, 228, 230 or a range consisting of any two of the values. R1 and R2 are within the above range, indicating that both the bare foil area and the coated area have good tensile strength; at the same time, 1.2R2<R1, indicating that the area near the first edge of the positive electrode material layer is no longer a "weak area" of the positive electrode sheet, and the tensile strength near the first edge is improved, which is beneficial to reduce the risk of positive electrode tab fracture and improve the safety performance of the secondary battery. In this application, the tensile strength of the coated area refers to the tensile strength of the coated area corresponding to the positive electrode material layer.
[0053] In the present application, adhesive tape is first pasted on the first and second regions of the positive electrode current collector, and then the adhesive tape and the positive electrode material layer on its surface are removed. After the adhesive tape is removed, the roughness of the empty foil area and the insulating layer corresponding to the surface of the positive electrode current collector in the first and second regions increases compared to the roughness of the surface of the positive electrode current collector without adhesive tape. In addition, during the preparation of the positive electrode sheet, the magnitude of the cold pressing pressure will also affect the roughness of the empty foil area. Specifically, in some embodiments of the present application, the roughness of the empty foil area of the positive electrode sheet is Rzμm, 2≤Rz≤5. For example, Rz can be 2, 2.5, 3, 3.5, 4, 4.5, 5, or a range consisting of any two values therebetween. When Rz is within the above range, the empty foil area can have better tensile strength and flatness, which is beneficial to improve the tensile strength near the positive electrode tab and reduce the risk of positive electrode tab breakage; in addition, the rougher empty foil area obtained is also beneficial to the adhesion of the subsequent insulating layer after coating, improves the bonding force between the insulating layer and the positive electrode current collector, reduces the risk of insulating layer falling off, and thus improves the safety performance of the secondary battery.
[0054] In some embodiments of the present application, the insulating layer includes an insulating layer binder and a ceramic material. Based on the mass of the insulating layer, the mass percentage content W1 of the insulating layer binder is 5% to 20%, for example, it can be 5%, 7%, 10%, 12%, 15%, 18%, 20% or a range consisting of any two values therebetween. By adjusting the mass percentage content of the insulating layer binder in the insulating layer within the above range, the adhesion between the positive electrode collector and the insulating layer can be improved, which is conducive to reducing the occurrence of short circuit between the positive electrode tab and the negative electrode sheet, and thus is conducive to improving the safety performance of the secondary battery.
[0055] In some embodiments of the present application, the insulating layer includes an insulating layer binder and a ceramic material, and based on the mass of the insulating layer, the mass percentage content W2 of the ceramic material is 80% to 95%, for example, it can be 80%, 82%, 85%, 88%, 90%, 93%, 95% or a range consisting of any two values therebetween. By adjusting the mass percentage content of the ceramic material in the insulating layer within the above range, the insulation performance between the positive electrode tab and the negative electrode sheet can be improved, thereby improving the safety performance of the secondary battery.
[0056] In some embodiments of the present application, the insulating layer includes an insulating layer binder and a ceramic material, and based on the mass of the insulating layer, the mass percentage W1 of the insulating layer binder is 5% to 20%, and the mass percentage W2 of the ceramic material is 80% to 95%. By adjusting the mass percentage of the binder and the ceramic material in the insulating layer within the above range, the insulating layer has good insulating properties and good adhesion with the positive electrode current collector, which is conducive to reducing the risk of short circuit between the positive electrode tab and the negative electrode sheet, and improving the safety performance of the secondary battery.
[0057] In some embodiments of the present application, the binder of the insulating layer includes at least one of polyurethane, polyacrylic acid or polyacrylonitrile. The insulating layer binder can not only better adhere the insulating layer to the surface of the positive electrode current collector, but also has good chemical stability and heat resistance, and can better adapt to the working environment of the positive electrode plate in the secondary battery. Therefore, by selecting the insulating layer binder, the insulating layer obtained has good adhesion to the positive electrode current collector, and the insulating layer is not easy to fall off when the secondary battery is working, thereby improving the cycle stability and safety performance of the secondary battery.
[0058] In some embodiments of the present application, the ceramic material includes at least one of boehmite or alumina. The ceramic material not only has good insulation performance at room temperature, but also exhibits good insulation performance at high temperature. Therefore, even when thermal runaway occurs in the secondary battery, it is still beneficial for the positive electrode tab and the negative electrode sheet to maintain good insulation performance, thereby improving the safety performance of the secondary battery.
[0059] In some embodiments of the present application, the binder of the insulating layer includes at least one of polyurethane, polyacrylic acid or polyacrylonitrile, and the ceramic material includes at least one of boehmite or alumina. When the binder is used in combination with the ceramic material, it is beneficial to further improve the insulation performance of the insulating layer, and can better reduce the risk of short circuit between the positive electrode tab and the negative electrode sheet, thereby improving the safety performance of the secondary battery.
[0060] In some embodiments of the present application, based on the mass of the insulating layer, the mass percentage W1 of the insulating layer binder is 70% to 90%, for example, it can be 70%, 72%, 75%, 78%, 80%, 82%, 85%, 87%, 90% or a range consisting of any two values therebetween. The mass percentage of the insulating layer binder is within the above range, indicating that the insulating layer has both good flexibility and adhesion. During the manufacturing process, the stress between the insulating layer and the positive electrode material layer can be moderately dispersed, and can adapt to a certain degree of micro-deformation of the positive electrode sheet during use, thereby improving the safety performance of the secondary battery. Furthermore, when the insulating layer binder includes at least one of the above-mentioned insulating layer binders, the insulating layer can have better flexibility, adhesion, chemical stability and heat resistance, and can adapt well to the processing process and working environment of the secondary battery, thereby improving the quality rate and safety performance of the secondary battery.
[0061] In some embodiments of the present application, based on the mass of the insulating layer, the mass percentage W2 of the ceramic material is 10% to 30%. For example, W2 can be 10%, 13%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or a range consisting of any two values therebetween. In the insulating layer, the mass percentage of the ceramic material is within the above range, which can control the insulation resistance of the insulating layer within the required range, improve the reliability of the insulating layer, and thus improve the safety performance of the secondary battery. Furthermore, the ceramic material includes at least one of boehmite or alumina, and the insulating layer has better insulation effect and heat resistance, which is conducive to further improving the safety performance of the secondary battery.
[0062] In some embodiments of the present application, based on the mass of the insulating layer, the mass percentage W1 of the insulating layer binder is 70% to 90%, and the mass percentage W2 of the ceramic material is 10% to 30%. By adjusting the mass percentage of the binder and the ceramic material in the insulating layer within the above range, it is beneficial to promote the insulating layer to have both good flexibility and insulation performance, and to enable the positive electrode tab and the negative electrode tab to maintain good insulation performance, while showing better flexibility to adapt to the deformation of the edge of the positive electrode tab, which is beneficial to improve the pass rate of the secondary battery in the drop test and improve the safety performance of the secondary battery.
[0063] In some embodiments of the present application, Figure 1 As shown, the edge of the insulating layer 30 close to the positive electrode material layer 20 is the third edge 31, and the third edge 31 coincides with the first edge 21. In some embodiments of the present application, Figure 2As shown, the edge of the insulating layer 30 close to the positive electrode material layer 20 is the third edge 31, and the third edge 31 is located between the first edge 21 and the second edge 22. The distance between the third edge 31 and the first edge 21 is s mm, 0≤s≤0.5. In some embodiments of the present application, 0≤s≤0.3. For example, the value of s can be 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 or a range consisting of any two values therebetween. Among them, the third edge coincides with the first edge, that is, s=0; the third edge is located between the first edge and the second edge, that is, 0<s≤0.5. In the present application, when setting the insulating layer, the insulating layer slurry is first set on the positive electrode current collector empty foil at a certain distance from the first edge of the positive electrode material layer. Since the insulating layer slurry is in a flowable state and has surface tension, the insulating layer slurry will spread and level in the direction of the positive electrode material layer until the third edge of the insulating layer coincides with the first edge of the positive electrode material layer, that is, s=0; or, the insulating layer slurry spreads along the first edge of the positive electrode material layer to the surface of the positive electrode material layer under the action of siphon, and penetrates into the positive electrode material layer under the action of gravity to form a new composite material layer, and the composite material layer is part of the insulating layer, so that the third edge of the insulating layer is located between the first edge and the second edge, that is, 0<s≤0.5. The surface of the above-mentioned composite material layer will present a color close to that of the insulating layer, and can be clearly observed and tested by a scanning electron microscope (SEM). Therefore, under the condition of controlling the amount of the insulating layer to be constant, the regulation of s can be achieved by controlling the distance between the position where the insulating layer slurry is initially set and the first edge. By adjusting the distance s between the third edge and the first edge within the scope of the present application, the risk of lithium plating in the secondary battery can be reduced, thereby improving the safety performance of the secondary battery, while also facilitating taking into account the energy density of the secondary battery.
[0064] In some embodiments of the present application, Figure 3 As shown, the positive electrode sheet 01 includes a positive electrode current collector 10 and a positive electrode material layer 20 and an insulating layer 30 respectively arranged on the two surfaces of the positive electrode current collector 10, the positive electrode material layer 20 includes a first positive electrode material layer 201 arranged on one surface of the positive electrode current collector and a second positive electrode material layer 202 arranged on the other surface of the positive electrode current collector, the insulating layer 30 includes a first insulating layer 301 arranged on one surface of the positive electrode current collector and a second insulating layer 302 arranged on the other surface of the positive electrode current collector, the first positive electrode material layer 201 and the first insulating layer 301 are located on the same side of the positive electrode current collector 10, and the second positive electrode material layer 202 and the second insulating layer 302 are located on the same side of the positive electrode current collector 10. Along the direction from the first positive electrode material layer 201 to the first insulating layer 301, that is, Figure 3In the direction indicated by the middle arrow, the distance between the third edge 31 of the first insulating layer 301 and the first edge 21 of the first positive electrode material layer 201 is s1, the distance between the third edge 31 of the second insulating layer 302 and the first edge 21 of the second positive electrode material layer 202 is s2, and the difference between the distances s1 and s2 is Δs mm, 0≤Δs≤0.3. In some embodiments of the present application, 0≤Δs≤0.1, for example, Δs can be 0, 0.02, 0.05, 0.07, 0.1, 0.12, 0.15, 0.18, 0.2, 0.23, 0.25, 0.28, 0.3 or a range consisting of any two values therebetween. By adjusting the distance Δs between the third edges of the insulating layer on both sides of the positive electrode current collector within the above range, the stress concentration near the first edge of the positive electrode material layer is alleviated, and the tensile strength near the first edge of the positive electrode material layer is increased, thereby reducing the risk of positive electrode tab fracture; at the same time, lithium deposition and black spots are not likely to occur during the secondary battery cycle, which is beneficial to improving the cycle stability and safety performance of the secondary battery. In addition, it is also beneficial to take into account the energy density of the secondary battery.
[0065] In some embodiments of the present application, the maximum thickness of the insulating layer is d μm, 10≤d≤40, in some embodiments of the present application, 10≤d≤25, for example, it can be 10, 15, 18, 20, 22, 25, 27, 30, 33, 35, 38, 40 or a range consisting of any two values therebetween. Figure 1 and Figure 2 As shown, due to the surface tension of the insulating layer slurry during the coating process, the thickness of the insulating layer 30 obtained is not uniform. Therefore, the outer contour of the insulating layer 30 is usually irregular. Figure 1 In the direction indicated by the middle arrow, the area from 21aμm away from the first edge to the surface intersection of the insulating layer 30 and the positive electrode current collector 10 is used as the area for evaluating the thickness parameters of the insulating layer 30. The above a=0.2, the maximum thickness of the insulating layer 30 in this area is d. The maximum thickness d of the insulating layer is regulated by regulating the coating amount of the insulating layer slurry. By controlling the maximum thickness d of the insulating layer within the above range, it is helpful to reduce the risk of short circuit between the positive electrode tab and the negative electrode sheet, and reduce the occurrence of current collector fracture during processing, thereby improving the safety performance and production process efficiency of the secondary battery.
[0066] In some embodiments of the present application, Figure 1 and Figure 2As shown, along the direction from the positive electrode material layer 20 to the insulating layer 30, the distance between the third edge 31 and the surface intersection of the above-mentioned insulating layer 30 and the positive electrode current collector 10 is the width b of the insulating layer 30. In some embodiments of the present application, the unit of width b is μm, 1.5≤b≤3.5. In some embodiments of the present application, 2.0≤b≤3.0. For example, 1.5, 1.7, 2, 2.3, 2.5, 2.8, 3, 3.2, 3.5 or a range consisting of any two values therebetween. Along the length direction of the positive electrode current collector, when the sum of the sizes of the positive electrode material layer and the insulating layer is constant, the size of b will affect the size of the positive electrode material layer, and thus affect the energy density of the secondary battery, and also affect the number of secondary batteries that pass the drop test. Therefore, by controlling the maximum thickness d and width b of the insulating layer within the above range, the energy density and safety performance of the secondary battery can be balanced, so that the secondary battery has a higher energy density while having a higher safety performance.
[0067] In some embodiments of the present application, Figure 3 and Figure 4 As shown, the positive electrode sheet 01 includes a positive electrode collector 10 and a positive electrode material layer 20 and an insulating layer 30 respectively arranged on the two surfaces of the positive electrode collector 10, the positive electrode material layer 20 includes a first positive electrode material layer 201 arranged on one surface of the positive electrode collector and a second positive electrode material layer 202 arranged on the other surface of the positive electrode collector, and the insulating layer 30 includes a first insulating layer 301 arranged on one surface of the positive electrode collector and a second insulating layer 302 arranged on the other surface of the positive electrode collector, the first positive electrode material layer 201 and the first insulating layer 301 are located on the same side of the positive electrode collector 10, and the second positive electrode material layer 202 and the second insulating layer 302 are located on the same side of the positive electrode collector 10. The maximum thickness of the first insulating layer 301 is d1, and the maximum thickness of the second insulating layer 302 is d2. The absolute value of the difference between d1 and d2 is Δd, in μm, and 0≤Δd≤15. In some embodiments of the present application, 0≤Δd≤10. In some embodiments of the present application, 0≤Δd≤5. For example, Δd can be 0, 2.5, 5, 7.5, 10, 12.5, 15, or a range consisting of any two values therebetween. By adjusting the value of Δd within the scope of this application, the uniformity of the insulating layer coating on both sides of the positive electrode current collector is better, which is not only conducive to improving the insulation performance between the positive electrode tab and the negative electrode sheet, but also conducive to improving the production process optimization rate of the secondary battery, improving the tensile strength near the positive electrode tab, reducing the risk of fracture of the positive electrode tab, and thus improving the safety performance of the secondary battery.
[0068] In some embodiments of the present application, Figure 3 and Figure 4As shown, the positive electrode sheet 01 includes a positive electrode collector 10 and a positive electrode material layer 20 and an insulating layer 30 respectively arranged on the two surfaces of the positive electrode collector 10, the insulating layer 30 includes a first insulating layer 301 arranged on one surface of the positive electrode collector and a second insulating layer 302 arranged on the other surface of the positive electrode collector, the width of the first insulating layer 301 is b1, the width of the second insulating layer 302 is b2, the absolute value of the difference between b1 and b2 is Δb mm, 0≤Δb≤0.3. In some embodiments of the present application, 0≤Δb≤0.1. For example, Δb can be 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3 or a range consisting of any two values therebetween. By regulating Δb within the above range, it is beneficial to the tensile strength near the first edge of the positive electrode material layer, which is beneficial to reducing the risk of fracture of the positive electrode ear and improving the safety performance of the secondary battery. In addition, Δb within the above range is also beneficial to the active ions of the secondary battery, such as lithium ions, to be better transmitted between the positive electrode plate and the negative electrode plate, thereby improving the energy density of the secondary battery.
[0069] In order to alleviate the problem of wrinkling and fracture of the positive electrode current collector caused by stress concentration at the edge of the positive electrode material layer during the manufacturing process of the secondary battery, a positive electrode current collector with a larger thickness, such as 12μm, is usually used. However, the use of such a thicker positive electrode current collector will significantly reduce the energy density of the secondary battery. In some embodiments of the present application, the thickness of the positive electrode current collector is hμm, 8≤h≤10, for example, h can be 8, 9, 10 or a range consisting of any two values therebetween. By selecting a positive electrode current collector within the above range, it is possible to alleviate the wrinkling of the empty foil area of the positive electrode sheet during the cold pressing process, reduce the risk of fracture of the positive electrode ear, improve the safety performance of the secondary battery, and also help to improve the energy density of the secondary battery.
[0070] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).
[0071] In the present application, positive electrode current collectors of different thicknesses can be purchased and measured with a micrometer to select a current collector of the desired thickness.
[0072] The positive electrode material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to at least one of lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate.
[0073] The positive electrode material layer may also include a conductive agent and a positive electrode binder. The present application has no particular restrictions on the types of conductive agents and positive electrode binders, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The positive electrode binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber or polyvinylidene fluoride. The present application does not particularly limit the mass ratio of the positive electrode active material, the conductive agent, and the positive electrode binder in the positive electrode material layer. Those skilled in the art can select according to actual needs as long as the purpose of the present application can be achieved.
[0074] The present application has no particular limitation on the thickness of the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode material layer is 30 μm to 120 μm.
[0075] Optionally, the positive electrode sheet may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited, and it can be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a positive electrode binder. The present application has no particular restrictions on the conductive agent and the positive electrode binder in the conductive layer, for example, it can be at least one of the above conductive agent and the above positive electrode binder.
[0076] A third aspect of the present application provides a secondary battery, which includes the positive electrode sheet in any of the aforementioned embodiments or the positive electrode sheet obtained according to the aforementioned preparation method.
[0077] In the present application, the secondary battery also includes a negative electrode plate, and the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer is disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or it can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode current collector, or it can be a partial area of the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.
[0078] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector. For example, the composite current collector may be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc.
[0079] The negative electrode material layer includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 Or at least one of Li-Al alloy.
[0080] In some embodiments of the present application, the negative electrode material layer may further include a conductive agent and a negative electrode binder. The present application does not particularly limit the types of the conductive agent and the negative electrode binder, as long as the purpose of the present application can be achieved. For example, it may be at least one of the above conductive agent and the above positive electrode binder. The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent, and the negative electrode binder in the negative electrode material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0081] The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode material layer is 30 μm to 120 μm. The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode current collector is 4 μm to 15 μm.
[0082] Optionally, the negative electrode sheet may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive agent and a negative electrode binder. The present application has no particular restrictions on the conductive agent and the negative electrode binder in the conductive layer, which may be, for example, at least one of the above conductive agent and the above negative electrode binder.
[0083] In the present application, the secondary battery also includes a diaphragm. The present application has no particular restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include, but is not limited to, polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) films), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of diaphragm may include at least one of a woven membrane, a nonwoven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0084] In some embodiments of the present application, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer may be a nonwoven fabric, a film or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0085] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0086] In some embodiments of the present application, the inorganic layer includes inorganic particles and a separator binder. The present application has no particular restrictions on inorganic particles, for example, inorganic particles may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the separator binder, for example, the separator binder may be at least one of the above-mentioned positive electrode binders. In some embodiments of the present application, the polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).
[0087] In the present application, there is no particular limitation on the thickness of the separator as long as the purpose of the present application can be achieved. For example, the thickness of the separator may be 3 μm to 30 μm.
[0088] In the present application, the secondary battery further includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent.
[0089] The present application has no particular restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the content of lithium salts in the electrolyte, as long as the purpose of the present application can be achieved.
[0090] The present application has no particular limitation on the non-aqueous solvent as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.
[0091] The carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or methyl ethyl carbonate (MEC). The cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.
[0092] The secondary battery also includes a shell for accommodating a positive electrode plate, a separator, a negative electrode plate and an electrolyte, as well as other components known in the field of secondary batteries, and this application does not limit the above-mentioned other components. This application does not particularly limit the shell, and it can be a shell known in the art, as long as the purpose of this application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal, and this application does not limit the type of metal. A metal hard shell known in the art can be used, as long as the purpose of this application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0093] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and there is no particular limitation in the present application. For example, the preparation process of the secondary battery may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire laminated structure with tape to obtain an electrode assembly of a laminated structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.
[0094] The fourth aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has good performance.
[0095] The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.
[0096] Example
[0097] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0098] Test methods and equipment:
[0099] Drop performance test:
[0100] The lithium-ion battery to be tested was placed in an environment of 25°C, charged at a constant current of 0.5C to a voltage of 4.5V, then charged at a constant voltage of 4.5V to a cut-off current of 0.05C, and left to stand for 5 minutes to be fully charged;
[0101] Place the lithium-ion battery in a fixed fixture, inspect its appearance and take photos before and after the test;
[0102] The tester was dropped from a height of 1.8m on a metal drop floor once along the head and tail, and once at the four corners. A total of 7 rounds of testing were conducted, with 6 times in 1 round. The drop order was: head->tail->right corner of the head->right corner of the tail->left corner of the head->left corner of the tail (angle: 45±15 degrees).
[0103] The voltage and internal resistance of the lithium-ion battery were measured after the drop test and 24 hours after the test. The criteria for passing the drop test were: no fire, no explosion, no smoke, no leakage, and a voltage drop of <50mV. Ten lithium-ion batteries were tested for each embodiment or comparative example, and the number of passed batteries was recorded, which was recorded as: the number of passed batteries / the number of experiments, such as 9 / 10 means that 9 lithium-ion batteries passed the test out of the 10 lithium-ion batteries tested.
[0104] Fracture position test, tensile strength test:
[0105] Under the condition of ambient temperature of 25℃ and ambient humidity of less than 2%, the lithium-ion battery was disassembled, the positive electrode sheet was taken out, the residual electrolyte on the surface of the positive electrode sheet was absorbed with dust-free paper, and the area including the positive electrode ear and the coating area in the positive electrode sheet was cut from the positive electrode material layer to the insulating layer as the test sample. The length of the sample was 30mm and the width was 5mm. The length of the corresponding area of the positive electrode material layer was 25mm and the width was 5mm. There was no obvious burr on the edge of the cut positive electrode sheet. Each lithium-ion battery was sampled for testing. The sample was fixed between the clamping terminals of the tensile testing machine (LJ2005), the limit block of the tensile testing machine was adjusted, and the speed was set to 10mm / min to start the test until the sample was broken, the fracture position was recorded, and the subsequent x test was carried out. At the same time, the tensile strength tested by the tensile testing machine was recorded.
[0106] x: Place the positive electrode material layer of the positive electrode sheet facing upwards under a VHX5000 microscope. During the observation process, adjust the microscope magnification within the range of 10 to 50 times until a photo showing both the first edge of the positive electrode material layer and the fracture position of the positive electrode sheet can be taken, and x is measured using the microscope software. If the edge of the fracture position is not neat, the closest distance to the first edge shall prevail. If the positive electrode material layer and the insulating layer are arranged on two surfaces of the coating area, and Δs>0, the distance between the first edge of the two surfaces and the fracture position is tested respectively, and the smaller one is recorded. The results of the four tests are recorded as x1, x2, x3, and x4, and finally the average of x1, x2, x3, and x4 is calculated as x.
[0107] (1) If the fracture position is between the first edge and the second edge of the positive electrode material layer and x>3, the tensile strength at this time is R2. Take another positive electrode sheet sample, which only includes the area where the insulating layer is set and the area of the positive electrode tab, and repeat the above steps to perform the tensile strength test. The tensile strength of the sample when it is broken is R1.
[0108] (2) If the fracture position is between the first edge and the empty foil area or between the first edge and the second edge and x≤3, the tensile strength at this time is R1. Take another sample, the positive electrode sheet sample only includes the area where the positive electrode material layer is set, and repeat the above steps to perform the tensile strength test. The tensile strength of the sample when it is broken is R2.
[0109] R1 and R2 were tested 4 times, and the average value of their tensile strength was taken as the final test result.
[0110] Roughness test:
[0111] At an ambient temperature of 25°C, the lithium-ion battery was disassembled, the positive electrode sheet was taken out, and it was soaked in dimethyl carbonate (DMC) for 20 minutes. Then the positive electrode sheet was placed in an oven and dried at 80°C for 12 hours. One surface of the empty foil area was facing up and fixed flatly on the stage; then the stage was placed flatly directly under the objective lens of the microscope (Keyence VXH-6000). Adjust the microscope, select the roughness test mode, and measure the roughness of the empty foil area near the junction of the positive electrode ear and the insulating layer at a magnification of 300 times. Repeat the test of three fields of view of the empty foil area, and take the average of the three tests as the roughness of the empty foil area of the positive electrode sheet.
[0112] Energy density test:
[0113] (1) Test of discharge capacity: At an ambient temperature of 25°C, charge the lithium-ion battery at a constant current of 1C to a voltage of 4.5V, then charge at a constant voltage of 4.5V to a cut-off current of 0.05C, let stand for 5 minutes, then discharge at a constant current of 0.2C to a voltage of 3.0V, let stand for 5 minutes, and record the discharge capacity at this time as C, in Wh.
[0114] (2) Lithium-ion battery size test: Figure 5, along the extension direction of the positive pole ear 70, i.e., the direction of the arrow in the figure, the lithium-ion battery 02 includes a fifth edge 401 and a sixth edge 601 opposite to each other, the edge of the positive pole ear 70 is set as the fifth edge 401, the area within 3 mm extending from the fifth edge 401 in the opposite direction of the extension direction of the positive pole ear 70 is the head area 40, the area within 3 mm extending from the sixth edge 601 in the extension direction of the positive pole ear 70 is the tail area 60, and the remaining area between the head area 40 and the tail area 60 is the middle area 50. The distance between the fifth edge 401 and the sixth edge 601 is the length L of the lithium-ion battery 02, the length of the fifth edge 401 is the width M of the lithium-ion battery 02, and the size of the lithium-ion battery 02 in the lamination direction is its thickness D. The length L and width M of the lithium-ion battery are respectively scanned and measured using a laser measuring instrument. The thickness Da of the head area 40, the thickness Db of the middle area 50, and the thickness Dc of the tail area 60 are measured with a micrometer, and the thickness of each area is measured 3 times. The average value of the 3 tests is taken as the thickness of the corresponding area. The thickness D of the lithium-ion battery is calculated by the following formula: D = 1 / 3 × (Da + Db + Dc). The units of D, L, and M are dm.
[0115] (3) Calculation of lithium-ion battery energy density X: X = C / (D×L×M);
[0116] The energy density X0 of comparative example 1 is recorded as "low", X0 = 712.7Wh / L, and each increase of 0.5% is a gradient of energy density. The energy density of the obtained lithium-ion battery is ranked from low to high as follows: high>upper middle>middle>lower middle>low. Among them, energy density greater than X0 and less than or equal to 1.005X0 is recorded as "lower middle", energy density greater than 1.005X0 and less than or equal to 1.010X0 is recorded as "middle", energy density greater than 1.010X0 and less than or equal to 1.015X0 is recorded as "upper middle", and energy density greater than 1.015X0 is recorded as "high".
[0117] Size Measurements:
[0118] d, b, s: The cross section of the positive electrode piece along the thickness direction is ion polished and the cross section of the electrode piece is observed and measured under a VHX5000 microscope at a magnification of 500. The above dimensions are measured at 10 points and the average value is taken as the final result.
[0119] Δd, Δb, Δs: Measure d1, d2, b1, b2, s1, s2 of the two surfaces respectively, and calculate Δd, Δb, Δs. Δd=|d1-d2|, Δb=|b1-b2|, Δs=|s1-s2|.
[0120] h: Use a micrometer to measure and take the average value of 10 points as the final result.
[0121] Example 1-1
[0122] <Preparation of Insulating Layer>
[0123] The insulating layer binder polyvinylidene fluoride and the ceramic material boehmite were mixed uniformly in an N-methylpyrrolidone (NMP) solvent at a mass ratio of 8:2 to obtain an insulating layer slurry with a solid content of 35 wt %.
[0124] <Preparation of positive electrode sheet>
[0125] Conductive carbon black and positive electrode binder polyvinylidene fluoride are mixed, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a conductive glue with a solid content of 7%. Lithium cobalt oxide, a positive electrode active material, is added to the conductive glue, and after vacuum stirring, a positive electrode material layer slurry with a solid content of 75% is obtained. The mass ratio of the positive electrode active material, the conductive agent and the positive electrode binder is 97:1:2.
[0126] Select a positive electrode current collector aluminum foil with a thickness h of 9μm. On one surface of the positive electrode current collector, stick a 10μm thick adhesive tape on the area of the positive electrode current collector corresponding to the empty foil area and the insulating layer. Then set the positive electrode material layer slurry in the third area. Along the direction from the insulating layer to the positive electrode material layer, the size of the positive electrode material layer slurry covering the adhesive tape is 8mm. Dry at 105℃ for 15min to obtain a positive electrode pole piece with a single-sided coating of a 75μm thick positive electrode material layer. Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode pole piece with a double-sided coating of a positive electrode material layer. Then perform a cold pressing treatment with a pressure of 90t, peel off the adhesive tape, and then apply the insulating layer slurry on the first edge of the positive electrode material layer on both sides of the positive electrode current collector, respectively. The coating amount of the insulating layer is 48mg / 1540.25mm 2 , and then dried to obtain the positive electrode sheet. The positive electrode sheet is cut into a fixed size, and the positive electrode ear is obtained by cutting from the corresponding position of the empty foil area, and then vacuum dried at 85°C for 4 hours to obtain a positive electrode sheet with a specification of 58mm×65mm for standby use. The thickness of the single-sided positive electrode material layer is 46μm, and the difference ΔT between the maximum thickness and the minimum thickness is 1μm. Specific parameters are shown in Table 1-1, Table 1-2 and Table 2. The thickness of the above-mentioned single-sided positive electrode material layer refers to the area in the positive electrode material layer except the edge area. The edge area is the area where the first edge extends 10mm from the insulating layer to the positive electrode material layer, and the area where the second edge extends 10mm from the positive electrode material layer to the insulating layer. The following embodiments and comparative examples are understood in the same way.
[0127] <Preparation of negative electrode sheet>
[0128] The negative electrode material artificial graphite, the binder styrene butadiene rubber and the binder sodium carboxymethyl cellulose are mixed in a mass ratio of 96:2:2, deionized water is added as a solvent, and the negative electrode slurry with a solid content of 45wt% is obtained after being stirred evenly. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 85°C to obtain a negative electrode sheet with a single-sided coating of a 100μm thick negative electrode material layer. Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a double-sided coating of a negative electrode material layer. After cold pressing, cutting, and cutting from the corresponding position of the empty foil area to obtain a negative electrode ear, vacuum drying at 120°C for 12h, a negative electrode sheet with a specification of 60mm×67mm is obtained for standby use.
[0129] <Preparation of Electrolyte>
[0130] In an environment with a water content of less than 10 ppm, ethylene carbonate, propylene carbonate, and diethyl carbonate are mixed in a mass ratio of 1:1:1 to obtain an organic solvent, and then electrolyte salt LiPF6 is added to the organic solvent and mixed evenly to obtain an electrolyte solution. The molar concentration of the electrolyte salt is 1.15 mol / L based on the mass of the electrolyte solution.
[0131] <Preparation of Separator>
[0132] A porous polyethylene film with a thickness of 7 μm (provided by Celgard Company) was used.
[0133] <Preparation of lithium-ion batteries>
[0134] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then the four corners of the entire stacked structure are fixed with tape to obtain the electrode assembly of the stacked structure, and then the multiple positive electrode tabs of the multiple positive electrode sheets are integrated and welded to obtain the positive electrode tab of the lithium-ion battery, and the negative electrode tabs of the multiple negative electrode sheets are integrated and welded to obtain the negative electrode tab of the lithium-ion battery; the electrode assembly is placed in an aluminum-plastic film outer packaging foil, and the moisture is removed at 80°C, and the prepared electrolyte is injected, and the soft-pack lithium-ion battery is obtained after vacuum packaging, standing, forming, shaping, capacity testing and other processes. Among them, the formation temperature is 80°C and the formation standing time is 2h.
[0135] Example 1-2 to Example 1-6
[0136] Except for adjusting the relevant preparation parameters according to Table 1-1, the rest is the same as Example 1-1.
[0137] Example 1-7 to Example 1-9
[0138] Except for adjusting the relevant preparation parameters according to Table 1-1, the rest is the same as Example 1-5. In the preparation process of the positive electrode sheet, after the positive electrode current collector is pasted with adhesive tape, the starting coating position of the positive electrode material layer slurry is changed so that the difference between the maximum thickness and the minimum thickness of the positive electrode material layer is as shown in Table 1.
[0139] Example 1-10 to Example 1-27
[0140] Except for adjusting the relevant preparation parameters according to Table 1-1, the rest is the same as Example 1-5. Among them, in Example 1-16 to Example 1-21, along the direction from the insulating layer to the positive electrode material layer, the sum of the sizes of the positive electrode material layer and the insulating layer is constant, and when b1 and b2 increase or decrease compared with Example 1-5, the size of the positive electrode material layer decreases or increases accordingly.
[0141] Example 1-28 to Example 1-39
[0142] Except for adjusting the relevant preparation parameters according to Table 1-2, the rest is the same as Example 1-5. Among them, in Example 1-36 to Example 1-38, along the direction from the insulating layer to the positive electrode material layer, the sum of the sizes of the positive electrode material layer and the insulating layer is constant, and when b2 decreases compared with Example 1-5, the size of the positive electrode material layer increases accordingly.
[0143] Example 2-1 to Example 2-5
[0144] Except for adjusting the relevant preparation parameters according to Table 2, the other embodiments are the same as Embodiment 1-5. In Embodiment 2-1 to Embodiment 2-3, the roughness of the empty foil area and the compaction density of the positive electrode material layer are as shown in Table 2 by changing the cold pressing pressure.
[0145] Comparative Example 1
[0146] Except for preparing the positive electrode sheet according to the following steps, the rest is the same as Example 1-5:
[0147] <Preparation of positive electrode sheet>
[0148] The positive electrode material layer slurry is the same as that of Example 1-1.
[0149] Select a positive electrode current collector aluminum foil with a thickness of 9μm, set the positive electrode material layer slurry on one surface of the positive electrode current collector, and dry it at 105℃ for 15min to obtain a positive electrode sheet with a single-sided positive electrode material layer of 75μm thickness. Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet with a "thinning area" with a double-sided positive electrode material layer, and then apply the insulating layer slurry on the first edge of the positive electrode material layer on both sides of the positive electrode current collector. The coating amount of the insulating layer is 48mg / 1540.25mm 2. Then dry it and then cold press it with a pressure of 90t to obtain the positive electrode sheet. Cut the positive electrode sheet into a fixed size, cut the positive electrode ear from the corresponding position of the empty foil area, and then vacuum dry it at 85°C for 4 hours to obtain a positive electrode sheet with a specification of 58mm×65mm for standby use. The specific parameters are shown in Table 1. The thickness of the single-sided positive electrode material layer is 46μm, and the thickness of the above-mentioned single-sided positive electrode material layer refers to the thickness of the positive electrode material layer from 10mm from the first edge to the second edge area.
[0150] Comparative Example 2
[0151] Except for preparing the positive electrode sheet according to the following steps, the rest is the same as Example 1-5:
[0152] <Preparation of positive electrode sheet>
[0153] The positive electrode material layer slurry is the same as that of Example 1-1.
[0154] Select a positive electrode current collector aluminum foil with a thickness h of 9μm, and stick a 10μm thick adhesive tape on the area of the positive electrode current collector corresponding to the empty foil area and the insulating layer. Then set the positive electrode material layer slurry on one surface of the positive electrode current collector. The positive electrode material layer slurry covers the adhesive tape and is dried at 105°C for 15 minutes to obtain a positive electrode pole piece with a single-sided coating of a 75μm thick positive electrode material layer. Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode pole piece with a double-sided coating of a positive electrode material layer. Then peel off the adhesive tape, and then apply the insulating layer slurry on the first edge of the positive electrode material layer on both sides of the positive electrode current collector. The coating amount of the insulating layer is 48mg / 1540.25mm 2 . Then. After drying, cold pressing treatment is carried out, and the pressure of cold pressing treatment is 90t to obtain positive electrode sheets. The positive electrode sheets are cut into fixed sizes, and the positive electrode ears are cut from the corresponding positions of the empty foil area, and then vacuum dried at 85°C for 4 hours to obtain positive electrode sheets with specifications of 58mm×65mm for standby use. The specific parameters are shown in Table 1. The thickness of the single-sided positive electrode material layer is 46μm.
[0155] The preparation parameters and performance tests of each embodiment and comparative example are shown in Table 1-1, Table 1-2 and Table 2.
[0156] Table 1-1
[0157]
[0158]
[0159] Note: In Comparative Example 1, the energy density is recorded as "low", which means that its energy density X0 = 712.7Wh / L.
[0160] Table 1-2
[0161]
[0162]
[0163] Note: In Table 1-2, d1=20μm, b1=2.5mm, s1=0.2mm.
[0164] It can be seen from Example 1-1 to Example 1-39 and Comparative Example 1 to Comparative Example 2 that in the above embodiments, during the preparation of the positive electrode sheets, by introducing adhesive tape before cold pressing, peeling off the adhesive tape after cold pressing, and then setting an insulating layer, the fracture positions of the positive electrode sheets obtained in the embodiments are all between the first edge and the second edge of the positive electrode material layer and 20≥x>3, and the obtained lithium-ion batteries have more passed the drop test. This shows that the tensile strength near the first edge of the positive electrode material layer of the present application is improved, the risk of positive electrode ear fracture is reduced, and the lithium-ion battery has higher safety performance. As can be seen from Comparative Example 1, Figure 6a As shown, the tensile strength of the empty foil area of the positive electrode sheet and the area where the insulating layer is set in the positive electrode sheet is lower as a whole. When the tensile strength test is performed, x≤3, that is, the positive electrode material layer breaks near the first edge, and there are many wrinkles and serious deformation at the junction of the coating area and the empty foil area. Figure 6b As shown, when the positive electrode sheets of Examples 1-5 were subjected to the tensile strength test, they were broken between the first edge and the second edge of the positive electrode material layer, and 20≥x>3, and more of them passed the lithium ion drop test. Figure 6a and Figure 6b In the figure, the areas with different colors from top to bottom are the empty foil area, the area with the insulating layer, and the area with the positive electrode material layer. This shows that the safety performance of the lithium-ion battery meeting the present application is improved, and the energy density of the lithium-ion battery is taken into account.
[0165] The difference between the maximum thickness and the minimum thickness of the positive electrode material layer usually affects the energy density and safety performance of the secondary battery. It can be seen from Examples 1-5, 1-7 to 1-9 that when the difference between the maximum thickness and the minimum thickness of the positive electrode material layer is within the scope of this application, the number of lithium-ion batteries obtained that pass the drop test is large, and a higher energy density is taken into account. This shows that when the difference between the maximum thickness and the minimum thickness of the positive electrode material layer is within the scope of this application, the lithium-ion battery obtained has higher safety performance and higher energy density. Figure 7a This is a tensile test curve of the positive electrode plate test sample in Example 1. Figure 7b It is a tensile curve test graph of the test sample of the positive electrode plate in Examples 1-5. The two tensile strength test curves in the tensile curve test graph are tensile strength test curves of the test sample in the same lithium-ion battery. Figure 7a , Figure 7b Area A in the middle is the empty foil area and the insulating layer, as well as the corresponding area within the 3mm area from the first edge along the insulating layer to the positive electrode material layer, and area B is the positive electrode material layer area from 3mm from the first edge along the insulating layer to the positive electrode material layer to the second edge. It can be seen from the figure that when stretched to the same degree, the tensile strength of the above embodiment is greater, while the comparative example breaks faster when subjected to the same tensile stress. This shows that the positive electrode sheet of the present application has a higher tensile strength, and the tensile strength near the first edge of the positive electrode material layer is improved, thereby reducing the risk of positive electrode ear fracture, thereby improving the safety performance of lithium-ion batteries.
[0166] In addition, the positive electrode sheets in Examples 1-1 to 1-39 did not have wrinkles during the cold pressing process, while Comparative Examples 1 and 2 had obvious wrinkles during the cold pressing process. Figure 8a and Figure 8b As shown, Figure 8a This is an electron microscope photograph of a sample obtained by cold pressing in Comparative Example 1 in which only a positive electrode material layer is provided on the surface of the positive electrode current collector. Figure 8b This is an electron microscope photograph of the sample obtained by setting only the positive electrode material layer on the surface of the positive electrode current collector in Examples 1-5 after cold pressing and removing the adhesive tape. As can be seen from the figure, the left side is the area coated with the positive electrode material layer, and the right side is the empty foil area. Comparative Example 1 was cold pressed without adhesive tape. The junction between the positive electrode material layer and the aluminum foil had many wrinkles and serious deformation, and there were several diagonal lines, indicating that during the cold pressing process, the stress concentrated at the first edge of the positive electrode material layer and deformation occurred, resulting in fewer lithium-ion batteries passing the drop test. In Examples 1-5, adhesive tape was first applied to the area corresponding to the empty foil area in the positive electrode current collector and the insulating layer in the positive electrode plate, and then cold pressed. The empty foil area adjacent to the first edge of the positive electrode material layer was relatively flat and had no wrinkles. This shows that the use of the positive electrode plate in the embodiment of the present application can improve the problem of stress concentration near the first edge during cold pressing, thereby reducing the risk of the positive electrode plate breaking near the first edge of the positive electrode material layer, thereby improving the safety performance of the lithium-ion battery. In addition, refer to Figure 8b In the empty foil area where no positive electrode material layer is provided, there is a fish scale-like morphology on its surface, which is mainly caused by sticking and removing the adhesive tape.
[0167] In the insulating layer of the positive electrode sheet, the type and content of the insulating layer binder and ceramic material usually affect the results of the drop test. It can be seen from Examples 1-1 to 1-6 that when the content of the insulating layer binder and ceramic material is within the scope of this application, the obtained lithium-ion battery passes the drop test in a large number and has a higher energy density, which means that when the content of the insulating layer binder and ceramic material is within the scope of this application, the obtained lithium-ion battery has better safety performance and takes into account the energy density. By comparing Examples 1-5 and 1-39, it can be seen that when the types of the insulating layer binder and ceramic material are within the scope of this application, the obtained lithium-ion battery passes the drop test in a large number and has a higher energy density, which means that when the types of the insulating layer binder and ceramic material are within the scope of this application, the obtained lithium-ion battery has better safety performance and takes into account the energy density.
[0168] The maximum thickness d of the insulating layer usually affects the safety performance and production process excellence of the lithium-ion battery, while the width b usually affects the energy density and safety performance of the lithium-ion battery. It can be seen from Examples 1-5, 1-10 to 1-15 that in the present application, d is less than or equal to the thickness of the positive electrode material layer, so the change of d has little effect on the volume energy density of the secondary battery, but when d is too large, such as Example 1-15, the risk of breaking the belt is prone to occur during mass production and affects the production process excellence of the positive electrode sheet. When the maximum thickness d of the insulating layer is within the scope of the present application, the number of lithium-ion batteries passing the drop test is more. Along the direction of the length of the positive current collector, the sum of the dimensions of the positive electrode material layer and the insulating layer is constant, so the change of b will affect the change in the dimension of the positive electrode material layer, and then affect the energy density of the secondary battery. It can be seen from Examples 1-5, 1-16 to 1-21 that the width b of the insulating layer is within the scope of the present application, and the number of lithium-ion batteries passing the drop test is large, and the energy density is high. This shows that when the values of d and b are within the range of the present application, the obtained lithium-ion battery has good safety performance and a balanced energy density.
[0169] The distance s between the third edge of the insulating layer in the positive electrode plate and the first edge of the positive electrode material layer usually affects the energy density and safety performance of the lithium-ion battery. It can be seen from Examples 1-5, 1-22 to 1-27 that when s is within the scope of this application, the obtained lithium-ion battery not only has a higher energy density, but also has better safety performance. When the value of s is too large, such as in Example 1-27, although it is beneficial to improve the safety performance of the lithium-ion battery, it will affect the transmission of lithium ions between the positive electrode plate and the negative electrode plate, thereby affecting the electrochemical performance of the lithium-ion battery.
[0170] It can be seen from Examples 1-5, 1-28 to 1-31 that when the positive electrode material layer and the insulating layer are arranged on the two surfaces of the coating area, and the distance Δs between the third edges of the insulating layers on both sides of the positive electrode current collector is within the scope of this application, the obtained lithium-ion battery not only has a higher energy density, but also has a higher number of passes in the drop test. This shows that the lithium-ion battery with Δs within the scope of this application has higher safety performance and takes energy density into account. In addition, when Δs is within the scope of this application, the obtained lithium-ion battery not only has a higher energy density, but also has better kinetic performance, and the risk of lithium deposition on the positive electrode sheet is smaller. As in Example 1-31, Δs is too large, and the obtained lithium-ion battery has poor kinetic performance. The positive electrode sheet removed after cycling has slight lithium deposition and black spots.
[0171] It can be seen from Examples 1-5, 1-32 to 1-35 that when the positive electrode material layer and the insulating layer are disposed on the two surfaces of the coating area, the difference Δd between the maximum thickness of the insulating layer on both sides of the positive electrode current collector is within the scope of this application, and the obtained lithium-ion batteries pass the drop test in greater numbers and have a higher energy density, which indicates that when Δd is within the scope of this application, the safety performance of the lithium-ion battery can be improved while taking into account the energy density. In addition, when Δd is within the above range, it indicates that the thickness consistency of the coating layer on both sides of the positive electrode sheet is better, and the positive electrode sheet is not prone to curling during the preparation process, thereby not easily affecting the process quality rate.
[0172] The width difference Δb on both sides of the current collector in the positive electrode sheet usually affects the safety performance of the lithium-ion battery. It can be seen from Examples 1-36 to 1-38 that when Δb is within the scope of the present application, the obtained lithium-ion battery has a larger number of passes and a higher energy density in the drop test, which indicates that the safety performance and energy density of the lithium-ion battery are taken into account.
[0173] Table 2
[0174]
[0175] Embodiment 1-5, embodiment 2-1 to embodiment 2-3 are to control the coating amount of the positive electrode material layer to remain unchanged, adjust the cold pressing pressure in the preparation process of the positive electrode sheet, and change the compaction density of the positive electrode sheet and the roughness of the empty foil area. It can be seen from the above embodiments that the roughness of the empty foil area of the positive electrode sheet of the above embodiments is within the scope of this application, the overall tensile strength R1 of the empty foil area and the area where the insulating layer is set in the positive electrode sheet is better than the tensile strength R2 of the area where the positive electrode material layer is set in the positive electrode sheet, and the fracture position is located between the first edge and the second edge of the positive electrode material layer when stretched, and 20≥x>3, and the number of lithium-ion batteries obtained that pass the drop test is greater, which shows that the roughness of the empty foil area within the scope of this application has a lower risk of fracture of the positive electrode ear of the lithium-ion battery, and has higher safety performance.
[0176] The thickness of the positive electrode current collector usually affects the tensile strength and energy density of the positive electrode sheet. It can be seen from Examples 1-5, 2-4 and 2-5 that the tensile strengths R1 and R2 change with the thickness of the current collector. When the thickness of the positive electrode current collector is adjusted within the scope of this application, the tensile strength of the positive electrode material layer coating area of the obtained positive electrode sheet can still be made better than the tensile strength of the empty foil area and the insulating layer coating area. The fracture positions of the positive electrode sheet are all in the positive electrode material layer coating area, and 20≥x>3. This shows that the lithium-ion battery within the scope of this application has higher safety performance and also has higher energy density.
[0177] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
[0178] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0179] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
Claims
1. A positive electrode sheet, comprising a positive electrode current collector, a positive electrode material layer, and an insulating layer, the positive electrode sheet further comprising a hollow foil area and a coating area, the positive electrode material layer and the insulating layer are located in the coating area, the insulating layer and the positive electrode material layer are connected and arranged, along the length direction of the positive electrode current collector, the insulating layer is closer to the hollow foil area than the positive electrode material layer; Along the direction from the positive electrode material layer to the insulating layer, the positive electrode material layer includes a first edge and a second edge relative to each other, and the first edge is close to the empty foil area; the positive electrode sheet is subjected to a tensile strength test along the direction, and the fracture position of the positive electrode sheet is located between the first edge and the second edge, and the distance between the fracture position and the first edge is x mm, 3<x≤20.
2. The positive electrode sheet according to claim 1, wherein: 5<x≤20。 3. The positive electrode sheet according to claim 1, wherein: The difference between the maximum thickness and the minimum thickness of the positive electrode material layer is less than or equal to 1 μm.
4. The positive electrode sheet according to claim 1, wherein: The tensile strength of the hollow foil area and the area in the positive electrode sheet where the insulating layer is provided as a whole is R1 MPa, the tensile strength of the area in the positive electrode sheet where the positive electrode material layer is provided is R2 MPa, 220≤1.2R2<R1≤280.
5. The positive electrode sheet according to claim 1, wherein: The roughness of the empty foil area is Rzμm, 2≤Rz≤5.
6. The positive electrode sheet according to claim 1, wherein: The insulating layer comprises a binder and a ceramic material, and the insulating layer satisfies at least one of the following characteristics: (1) Based on the mass of the insulating layer, the mass percentage W1 of the binder is 5% to 20%; (2) Based on the mass of the insulating layer, the mass percentage W2 of the ceramic material is 80% to 95%.
7. The positive electrode sheet according to claim 1, wherein: The insulating layer comprises a binder and a ceramic material, and the insulating layer satisfies at least one of the following characteristics: (1) Based on the mass of the insulating layer, the mass percentage W1 of the binder is 70% to 90%; (2) Based on the mass of the insulating layer, the mass percentage W2 of the ceramic material is 10% to 30%.
8. The positive electrode sheet according to claim 6 or 7, wherein the insulating layer satisfies at least one of the following characteristics: (1) The binder comprises at least one of polyvinylidene fluoride, polyurethane, polyacrylic acid or polyacrylonitrile; (2) The ceramic material includes at least one of boehmite and alumina.
9. The positive electrode sheet according to any one of claims 1 to 7, wherein the maximum thickness of the insulating layer is d μm and the width is b mm, wherein: 10≤d≤40, 1.5≤b≤3.
5.
10. The positive electrode sheet according to claim 9, wherein: 10≤d≤25; and / or, 2.0≤b≤3.
0.
11. The positive electrode sheet according to any one of claims 1 to 7, wherein: The edge of the insulating layer close to the positive electrode material layer is a third edge, and the third edge coincides with the first edge, or the third edge is located between the first edge and the second edge, and the distance between the third edge and the first edge is s mm, 0≤s≤0.
5.
12. The positive electrode sheet according to claim 11, wherein: 0≤s≤0.3。 13. The positive electrode sheet according to claim 11, wherein the positive electrode material layer and the insulating layer are disposed on two surfaces of the coating area, and has at least one of the following characteristics: (1) Along the direction, the distance between the third edges of the insulating layer on both sides of the positive electrode current collector is Δs mm, 0≤Δs≤0.3; (2) The maximum thickness difference between the insulating layers on both sides of the positive electrode current collector is Δd μm, 0≤Δd≤15.
14. The positive electrode sheet according to claim 13, which satisfies at least one of the following characteristics: (1)0≤Δs≤0.1; (2)0≤Δd≤10.
15. The positive electrode sheet according to claim 13, wherein: The positive electrode material layer and the insulating layer are arranged on two surfaces of the coating area, and the difference in width of the insulating layer on both sides of the positive electrode current collector is Δb mm, 0≤Δb≤0.
3.
16. The positive electrode sheet according to claim 1, wherein: The difference between the maximum thickness and the minimum thickness of the positive electrode material layer is less than or equal to 0.8 μm.
17. A method for preparing a positive electrode sheet according to any one of claims 1 to 16, comprising the following steps: Obtaining positive electrode material layer slurry and insulating layer slurry; The adhesive paper is arranged in the first and second regions of the positive electrode current collector, and then the positive electrode material layer slurry is arranged in the third region of the positive electrode current collector so that at least part of the surface of the adhesive paper is covered by the positive electrode material layer slurry, and then dried and cold pressed, and then the adhesive paper is peeled off, and the insulating layer slurry is arranged in the second region, and dried to obtain the positive electrode sheet; The first area is an empty foil area, the second area is used to set the insulating layer, the third area is used to set the positive electrode material layer, and the first area, the second area and the third area are connected in sequence. 18 . A secondary battery comprising the positive electrode sheet according to claim 1 or the positive electrode sheet obtained by the preparation method according to claim 17 .
19. An electronic device comprising the secondary battery according to claim 18.
Citation Information
Patent Citations
Adhesive tape, preparation method of adhesive tape and preparation method of lithium ion battery
CN115466581A
Columnar battery and electric device comprising same
CN115911256A
Cited By
Battery monomer, battery device and electric device
CN121617900A
Battery cell, battery device, and electric device
CN121617900B
Positive electrode sheet, preparation method therefor, secondary battery, and electronic apparatus
WO2026157983A1